Analysis of Homeopathic Genus Epidemicus for COVID-19 Patients in Spain - Clapers, Marc Lluís; Velat, Manuela; Clapers, Josep Maria; Vidal-Jové, Joan; Mora, Joan (Homeopathy, 2021)
Background Homeopathy has had documented success treating epidemics in the last two centuries. We aimed to obtain a clear homeopathic clinical picture of coronavirus disease 2019 (COVID-19) and postulate the genus epidemicus of the disease in order to inform and enhance future treatment and prophylaxis options.Methods We conducted a prospective case series study, collecting data from 19 homeopaths in Catalonia, Spain, from patients who presented with fever and/or cough and/or breathlessness and/or confirmed COVID-19 infection or close contact with a confirmed case. We included 107 patients, and data were recorded through a checklist questionnaire on the day of the case analysis and at day 10–15 after commencing treatment. Symptoms were collected and analyzed with the help of homeopathic repertories.Results A total of 103 cases were mild or moderate; four were severe. The severe cases were excluded from the analysis and the 103 mild and moderate cases were analyzed and a clear overall clinical picture with mental, general, and particular symptoms was achieved. Eighty-eight cases had a complete recorded follow-up. The most prescribed medicines were Bry, Ars, Phos and Gels, whilst those with the best rates of good response were Sulph, Puls and Bry. Time to full recovery after homeopathic treatment ranged from 3.5 to 14.4 days, depending on the medicine used. The potency 200c was associated with faster rates of full recovery and a lesser need to change remedy.Conclusion We have defined the symptomatic homeopathic characteristics of mild and moderate COVID-19 in Spain and established a set of medicines that might be useful to consider as effective genus epidemicus.
Keywords: genus epidemicus; COVID-19; homeopathy